Administrative Data Linkage in Brazil: Potentials for Health Technology Assessment - Ali, M Sanni; Ichihara, Maria Yury; Lopes, Luciane Cruz; Barbosa, George C.G.; Pita, Robespierre; Carreiro, Roberto Perez; dos Santos, Djanilson Barbosa; Ramos, Dandara; Bispo, Nivea; Raynal, Fabiana; Canuto, Vania; de Araujo Almeida, Bethania; et al. (Frontiers in Pharmacology, 2019)
Health Technology Assessment (HTA) is the systematic evaluation of the properties and impacts of health technologies and interventions. In this article, we presented a discussion of health technology assessment and its evolution in Brazil, as well as a description of secondary data sources available in Brazil with potential applications to generate evidence for health technology assessment and policy decisions. Furthermore, we highlighted record linkage, ongoing record linkage initiatives in Brazil, and the main linkage tools developed and/or used in Brazilian data. Finally, we discussed the challenges and opportunities of using secondary data for research in the Brazilian context. In conclusion, we emphasized the availability of high quality data, an open, modern attitude towards the use of data for research and policy. This is supported by a rigorous but enabling legal framework that will allow the conduct of large scale observational studies to evaluate clinical, economical and social impacts of health technologies and social policies.